The Effect of Using Wattpad on Process-Genre Approach towards Writing Achievement in Tertiary Level - Rendhi Fatrisna Yuniar; Utami Widiati; Utari Praba Astuti (Jurnal Pendidikan: Teori, Penelitian, dan Pengembangan, 2019)
Abstract: This paper presents the integration between the use of technology and conventional learning and teaching process. Taking advantage of technology in classroom like the use of Wattpad by integrating with process-genre approach helps students to make the classroom activities become more efficient. This objective of this paper is to show the effect of using Wattpad in teaching and learning process by integrating with process-genre approach towards students’ writing achievement. The treatment starts from pre-test, and end with post-test. The result in this study shows after the students teach by using Wattpad gain better writing achievement than before using it.  Abstrak: Penelitian ini berisi tentang integrasi antara penggunaan teknologi dan pembelajaran konvensional pada proses pembelajaran. Mengambil kelebihan dari teknologi pada pembelajaran di kelas, seperti penggunaan Wattpad dengan mengintegrasikan pendekatan Process-genre, hal ini meningkatkan tingkat keefisiensian kegiatan pemblejaran di kelas. Penelitian ini bertujuan untuk melihat keefektifan penggunaan Wattpad yang diintegerasikan dengan pendekatan process-genre pada proses pembelajaran terhadap penacapaian menulis siswa. Penelitian yang dilakukan dimulai dari pretest dan diakhiri dengan posttest. Hasil dari penelitian ini menunjukkan siswa yang telah belajar menggunakan Wattpad memiliki pencapaian menulis yang lebih baik daripada sebelum menggunakannya.